Implementation of the design thinking process approach to improve crimping production working systems on lathes machines - Primasari, Monica Sandra; Kurnianingtyas, Chandra Dewi; Kurnia, Hibarkah (OPSI, 2024)
Fulfillment of orders for a product in the lathe industry often misses the processing deadline because the production process time is not well measured. One of the products produced by a lathe is crimping, this product often takes a long production process until 23.80 working hours. The purpose of this research is to identify the problems that cause the standard time for the crimping process to be high and provide the best solution for companies to reduce the standard time for the crimping production process. This research method uses the Design Thinking Process (DTP) which is divided into 5 stages, including Empathize, Define, Ideate, Prototype, and Test also called the EDIPT stage. The application of the EDIPT method also uses several methods or improvement tools. The improvements that have been made by the company are from the causes of methods, humans, and the environment. This research has resulted in a decrease in the standard time for the crimping process which originally obtained a processing time in 1 product of 1,428 minutes, while the standard time for the implementation of improvements was 1,375 minutes, so this research has succeeded in reducing the standard time in the crimping production process or reducing CSF by 3.71%.